Discussion on Radio: Peran Generasi Muda dalam Menjaga Lingkungan - Ramdani, Rizal; Yuliana, Ika; Alpiansah, Restu; Agus Pratama, Aryan; Dewi, Puspita (Insan Kreasi Media, 2024)
The young generation was an agent of change demanding environmental hygiene, which was particularly vital to disease prevention efforts. Besides, young representatives from diverse groups were advocating for environmental restoration and preservation out of concern for the potential consequences of climate change on the global community in the future. Thus, the article's objective was to introduce the young generation to the significance of environmental protection and influence their perspective on beginning to safeguard the earth at a young age. Also, the article's objective was to disseminate information regarding the implementation of the concept of environmental protection, which was transmitted and disseminated on the radio via a sharing session. The approach method utilized in this article is a shared session, presented in the manner of a Talk Show. Therefore, the young generation were spearheading the effort to address climate change with enthusiasm, ingenuity, and an unyielding dedication to a sustainable trajectory. The youth's crucial position on the environment will solve climate change, emphasizing their contributions, obstacles, and the significance of their participation in shaping a more favorable future for future generations.